An Introduction to Reverse Engineering Method in Codicology - mohamad reza vasfi (تحقیقات کتابداری و اطلاع‌رسانی دانشگاهی, 2011)
Objective: The outliving manuscripts have not enjoyed the same future. Although some manuscripts are favored with accurate information paving the way for researchers’ studies, for a considerable number of which, there is not enough information available. Some manuscripts are wrongly associated with false authors; the real authors of which are anonymous. A great number of manuscripts have been partly or wholly destroyed by natural and unnatural phenomena as well. Methodology: The present study aims at evaluating the data reported from manuscripts adopting a method which has recently been referred to as ‘Reverse Engineering’ in engineering sciences. Through this method, based on ‘mere technology’ or ‘technology accompanied by other majors and fields of study’, it would be possible to increase the scientific facets of codicologistic studies. Consequently, it would be possible to report on the non-authenticity or counterfeiters of manuscripts. Findings: the researcher has tried to utilize the books and articles available in the two majors of “Librarianship Sciences” as well as “Engineering Sciences.” It can be concluded that the borderlines between phraseology, research, and the criticism are not crystal-clear revealing a direct relationship between reverse engineering and codicology.